2022
DOI: 10.4103/njms.njms_9_22
|View full text |Cite
|
Sign up to set email alerts
|

Can topical phenytoin combined with tetracycline enhance the healing process in medication-related osteonecrosis of jaw? A comparative study

Abstract: Introduction: Treatment of Medication-related osteonecrosis of the jaw (MRONJ) is challenging. The aim of this study was to assess the effect of topical phenytoin on the healing process of MRONJ after debridement. Materials and Methods: In this study, patients with stage II of MRONJ were randomly allocated to two groups: Group 1 received debridement of the necrotic bone, with additional 5% topical phenytoin + tetracycline. Patients in group 2 underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The results of this study showed that debridement, along with local administration of phenytoin and tetracycline, improved the healing process and the recurrence rate after treatment in medication-related osteonecrosis of the jaw (MRONJ) patients 26 . Considering that the wounds of diabetics have a prolonged inflammatory phase, phenytoin is beneficial for people with diabetes due to its anti-inflammatory action.…”
Section: Discussionmentioning
confidence: 90%
“…The results of this study showed that debridement, along with local administration of phenytoin and tetracycline, improved the healing process and the recurrence rate after treatment in medication-related osteonecrosis of the jaw (MRONJ) patients 26 . Considering that the wounds of diabetics have a prolonged inflammatory phase, phenytoin is beneficial for people with diabetes due to its anti-inflammatory action.…”
Section: Discussionmentioning
confidence: 90%